Ga3+ loaded radiation crosslinked gel-Alg-CMC hydrogels for promoting diabetic wound healing. (April 2023) - Chen, Gong; Ren, Kang; Wang, Hongjian; Wu, Lihao; Wang, Dai; Xu, Ling
The metal gallium holds great promise in the fight against infection by disrupting bacterial iron metabolism through a "Trojan horse" technique. It is well worth trying to investigate the potential for gallium-mediated hydrogels for the treatment of infected wounds. In this paper, Ga 3+ is innovatively given an important role in hydrogels based on the conventional multi-component hydrogel with metal ion binding gelation strategy. Thus, Ga@Gel-Alg-CMCs hydrogel with broad-spectrum antimicrobial activity is reported on the treatment of infected wounds. The morphology, degradability, and swelling behavior together indicated the excellent physical properties of this hydrogel. Interestingly, in vivo results also showed favorable biocompatibility, slowing down wound infection and promoting diabetic wound healing, making the gallium-doped hydrogel an ideal antimicrobial dressing.